Functional expression and photoaffinity labeling of a cloned P2U purinergic receptor. - Erb, L (1993)
ATP and UTP can function as extracellular signaling molecules by activating plasma membrane receptors termed P2 purinergic receptors. In the present study a P2U receptor cDNA has been expressed in K-562 human leukemia cells, one of the few available mammalian cell lines that lacks an endogenous P2U receptor. In stably transfected cells, low micromolar concentrations of ATP or UTP activated the receptor, resulting in the mobilization of intracellular calcium but not the influx of extracellular calcium. A photoaffinity agonist of the P2U receptor, 3'-O-(4-benzoylbenzoyl)adenosine 5'-[alpha-32P]triphosphate ([alpha-32P]BzATP), photolabeled several proteins in plasma membranes from the stable transfectant or from untransfected K-562 cells. The photolabeling of a 53-kDa protein was significantly greater in plasma membranes from the stable transfectant than from untransfected cells. A mutant receptor containing six consecutive histidine residues at its carboxyl terminus was constructed and used to verify that this 53-kDa protein was the P2U receptor. In plasma membranes from cells expressing the histidine-tagged P2U receptor, but not from cells expressing the wild-type receptor, a single [alpha-32P]BzATP-labeled protein with a molecular mass of 53 kDa was retained on a Ni(2+)-charged Sepharose column, which binds many proteins containing a polyhistidine tag. Photolabeling of the 53-kDa protein by [alpha-32P]BzATP was inhibited by ATP but not by UTP, raising the possibility that the P2U receptor may have distinct binding sites for each nucleotide.